The Price Sensitivity of Health Plan Choice: Evidence from Retirees in the German Social Health Insurance - Amelie C. Wuppermann; Sebastian Bauhoff; Markus M. Grabka (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
We investigate two determinants of the price sensitivity of health plan demand: the size of the choice set and the salience of premium differences. Using variation in both features in the German Social Health Insurance (SHI) and information on health plan switches of retirees in the German Socio Economic Panel, augmented with information on individuals' choice sets we find that retirees react less to potential savings from switching when they have more plans to choose from and when differences between premiums are less salient. Simplifying choices could save consumers money and improve the functioning of the health insurance market.
urn:nbn:de:bvb:19-epub-21080-8
Keywords: I11; D12; I18; 330; health plan choice; choice architecture; German social health insurance